Characterization of Key Odorants in Soy Sauce and Their Concentration Changes during Storage - Rui Wang; Shiyu Chang; Miao Liang; Yajian Wu; Runhu Xin; Yuping Liu; Liang Chen; Shangting Zhou (Journal of Food Quality)
To explore the key odorants and their concentration changes in high-salt liquid-state fermentation soy sauce (HLFSS) during storage, solvent extraction coupled with solvent-assisted flavor evaporation was applied to isolate the volatiles in HLFSS, and the volatiles were analyzed by gas chromatograph-mass spectrometry-olfactory and gas chromatograph-flame ionization detector-olfactometry combined with the aroma extract dilution assay. A total of 37 odor-active compounds with flavor dilution (FD) factors ranging from 1 to 1024 were identified, and 23 aroma components with odor activity values ≥1 were considered as key odorants. Methional, 3-methylbutanoic acid, phenethyl alcohol, sotolon, 4-hydroxy-2-methyl-5-ethyl-3(2H)-furanone (HEMF), and 4-hydroxy-2,5-dimethylfuran-3(2H)-one (HDMF) had the highest FD factors of 1024. The results of quantitative analysis through the internal standard curve showed that the concentrations of HEMF, HDMF, acetic acid, 1-hydroxy-2-butanone, acetol, and furfuryl alcohol varied greatly during storage, so these compounds might be used as the indicators to determine the shelf life of HLFSS. The recombination experiment also confirmed the important contribution of these compounds. This result will provide valuable information for understanding the flavor changes of HLFSS.